THE IRAQI AGRICULTURAL SECTOR AND ITS CONTRIBUTION TO THE GROSS DOMESTIC PRODUCT (GDP) FOR THE PERIOD 2000 TO 2022 - Saadia Hilal Hassan; Hani Abdul Rasoul Mohammed (Scholar Express Journals, 2024)
Translation to English: From the year 2000 to 2022, the Iraqi agricultural sector witnessed significant developments and faced several challenges influenced by the economic and political conditions in the country. The agricultural sector played a prominent role in contributing to the gross domestic product (GDP), but the extent of this contribution was affected by various factors. At the beginning of this period, the agricultural sector played a crucial role in achieving food self-sufficiency and significantly contributed to the GDP. However, the sector faced substantial challenges over the years, such as the impact of internal conflicts and changes in weather conditions, affecting crop production and exacerbating poverty levels in rural communities. Despite these challenges, the Iraqi government took measures to enhance the agricultural sector, including supporting farmers and improving agricultural infrastructure. New techniques and diverse crop cultivation were introduced, and investments were made in water infrastructure and irrigation systems. As time passed, other sectors of the Iraqi economy began to take precedence, leading to a relative decline in the agricultural sector's contribution to the GDP. Attention shifted towards oil and industrial sectors, causing disparities in sectoral contributions. In conclusion, the Iraqi agricultural sector remains a crucial part of the economy, and despite the challenges faced from 2000 to 2022, it continues to play a vital role in providing food and improving living conditions in the country
Keywords: Iraqi agricultural sector; Gross Domestic Product; Economic impact